2022
DOI: 10.7150/ijbs.75056
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID and its Management

Abstract: The pandemic of COVID-19 is the biggest public health crisis in 21 st Century. Besides the acute symptoms after infection, patients and society are also being challenged by the long-term health complications associated with COVID-19, commonly known as long COVID. While health professionals work hard to find proper treatments, large amount of knowledge has been accumulated in recent years. In order to deal with long COVID efficiently, it is important for people to keep up with current progresses and take proact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 130 publications
3
77
0
2
Order By: Relevance
“…A recent study developed a perdition model and concluded that the Omicron variant would cause substantial surges in hospitalizations, ICU admissions, and deaths, and would overwhelm the healthcare system; in fact, the Omicron wave would lead to approximately 1.55 million deaths if the dynamic zero-COVID strategy were rejected [ 17 ]. Moreover, besides the acute symptoms related to the infection, the long-term health complications of COVID-19, namely long COVID, is also a big challenge for the public health community [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study developed a perdition model and concluded that the Omicron variant would cause substantial surges in hospitalizations, ICU admissions, and deaths, and would overwhelm the healthcare system; in fact, the Omicron wave would lead to approximately 1.55 million deaths if the dynamic zero-COVID strategy were rejected [ 17 ]. Moreover, besides the acute symptoms related to the infection, the long-term health complications of COVID-19, namely long COVID, is also a big challenge for the public health community [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long COVID reflects chronic damage to multi-systemic organs [ 128 ]. The main pulmonary outcomes are dyspnea, ventilator and/or oxygen requirement, pulmonary function test (PFT) abnormalities and fibrotic lung disease [ 129 , 130 ]. Furthermore, hypercoagulability predisposes the patient to the risk of thrombosis within the small vessels of the pulmonary vasculature [ 129 , 131 ].…”
Section: Long Terms Consequencesmentioning
confidence: 99%
“…The main pulmonary outcomes are dyspnea, ventilator and/or oxygen requirement, pulmonary function test (PFT) abnormalities and fibrotic lung disease [ 129 , 130 ]. Furthermore, hypercoagulability predisposes the patient to the risk of thrombosis within the small vessels of the pulmonary vasculature [ 129 , 131 ]. Cardiovascular system sequelae include interstitial inflammatory infiltration, myocardial hypertrophy and necrosis [ 106 ], as well as myositis, cell death and, finally, fibrosis with the consequent increased risk of arrhythmias.…”
Section: Long Terms Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is known that SARS-CoV-2 infection could also cause many other long-term effects, collectively called "Long COVID". Koc et al 16 reviewed the general background of Long COVID, and discussed its risk factors, diagnostic indicators and management strategies. Park et al 17 reviewed anosmia, i.e., impairment of smell caused by olfactory dysfunctions, which is a common symptom of the Long COVID.…”
mentioning
confidence: 99%